أصول الدوحة و قطر البيوت الثراثية القطرية - Mariam Al Thani (16020516) (2023)
This item is an Illustrated Presentation produced by UCL Qatar as part of the The Origins of Doha and Qatar Project, and is part of Origins of Doha and Qatar: Traditional Qatari Homes School Pack - Arabic collection.  The Illustrated Presentation is for 6 - 11 years age groups. This work was illustrated by Sumam Azzam.